Hand Gesture Recognition based on Real-time Indian Sign Language - BS, Rakesh; S, Tamilarasan; N, Avinash (International Journal of Computer Sciences and Engineering, 2019)
Indian sign language (ISL) could be a language which is used to employ by hearing and speech impaired individuals to speak with other individuals. In this paper we present system which might recognise hand poses and gestures from the Indian sign language (ISL) in real-time mistreatment grid-based options. Here, we are introducing hand gesture recognition system to recognize the gestures and convert them to a natural language. Gesture recognition can be used to communicate merely through gestures without any physical link with the actual machine. Gesture is converted to text which helps deaf-dumb people to communicate with normal people. The system can be programmed in such a way that it can translate gesture to text. The proposed system involves taking the input through the in-built camera. One of the advantage of the system is that the individual can add new sentences based on their comfort and understanding. The output text is displayed on the screen based on the gesture showed to the camera.